Language use and gender representation in Harry Potter and The Deathly Hallow - Moesha Mukhliz, Siti Maryam; Sahar, Rafidah (Kulliyyah of Languages & Management (KLM), International Islamic University Malaysia, Edu Hub Pagoh, 84600 Muar, Johor Darul Takzim., 2021)
This study was conducted to identify the linguistic gender features used to represent the male and female characters in J. K Rowling’s Harry Potter and the Deathly Hallows novel. A qualitative content analysis was employed whereby a close reading of the novel was performed and linguistic gender differences between male and female characters are theorised based on Jennifer Coates’ (2015) works on conversational strategies. Findings revealed that male characters outperformed female characters in terms of their use of all seven linguistic features namely: minimal responses, hedges, tag questions, questions, commands and directives, swearing and taboo words, and compliments. The findings imply that authors and publishers of children's literature should make a greater effort to offer youngsters with material that uses gender-neutral language in order to eliminate gender prejudice and stereotypes.